Incidental and intentional learning of vocabulary among young ESL learners - Pavani Meganathan,; Ngee, Thai Yap; Shamala Paramasivam,; Ilyana Jalaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Developing a rich vocabulary repertoire in English is an essential achievement for young learners acquiring English as a second language (ESL) as having a strong word knowledge base supports the development of the four language skills in the second language. Most studies on vocabulary learning, however, have been conducted with adult learners at the college levels. The primary purpose of this study is to investigate the effectiveness of different instructional techniques (incidental learning and intentional learning) on vocabulary acquisition among young ESL learners. The participants were 99 students between 10-11 years old in a Malaysian Tamil primary school. Stratified sampling was applied, and the subjects were divided into 3 groups; a control group and two experimental groups: extensive reading (ER) and extensive reading plus vocabulary enhancement (ER+). The ER group received treatment involving extensive reading of storybooks while, the ER+ group received treatments involving extensive reading of storybooks and vocabulary enhancement activities. The treatments were conducted as after-class activities. The control group did not attend the after-class activity but continued with regular class activities. The vocabulary levels test (VLT) was administered to all groups before and after the treatment to measure the significant difference between the three groups. The results show a significant gain for both the experimental groups with the ER+ group having higher means in both the posttest and delayed post-test scores. However, there was no gain recorded for the control group. The study provides evidence that extensive reading can enhance vocabulary learning but the blending with vocabulary enhancement activities was more effective.